Effects of parental age and hatching egg weight of japanese quails on hatchability and chick weight - Seker, I.; Kul, S.; Bayraktar, M. (Asian Network for Scientific Information, 2004)
This investigation was carried out to determine the effects of the parental age and the hatching egg weight of the Japanese quails on the one-day old chick weight and fertility, hatchability of incubated eggs, hatchability of fertile eggs, the embryo mortalities in early middle and late periods and also some hatchability characteristics. The egg material of this investigation consisted of 2031 eggs obtained from the Japanese quails at the age of 10 weeks (1st parental age group) and at the age of 20 weeks (2nd parental age group). The eggs were grouped according to their weight as follows; 9.50-10.50, 10.51-11.50 and 11.51-12.50 g. Even if the differences related to the chick weight among the age groups were not statistically significant, the differences that were statistically significant (P<0.05) were found among the egg weight groups. The parental age had the statistically significant effect on the fertility (P<0.01) and hatchability of fertile eggs (P<0.05). In addition, the effect of the parental age on the hatchability of incubated eggs and the embryo mortalities was not found statistically significant (P>0.05). Even if the significant differences in the different levels (P<0.05, P<0.001) statistically were observed from the point of the generally analyzed hatching characteristics among the egg weight groups, any difference related to the early period embryo mortality was not determined as statistically significant. Results obtained from this study indicated that the parental age of Japanese quails of 10 and 20 weeks has not a significant effect on the one-day old chick weight. However, it had a significant effect on only the fertility and hatchability of fertile eggs. The effect of the egg weight had a very significant level on the chick weight so it was observed that the chick weight increased in parallel of increasing the egg weight. In addition, the egg weight had a significant effect on every aspect except the early stage embryo mortality as one of the hatching characteristics. © Asian Network for Scientific Information, 2004.
Keywords: Chick weight; Egg weight; Hatchability; Parental age; Quail